The role of principal leadership in enhancing personal development: an analysis of bottlenecks, lags, issues and concerns (BLICS) - Osias Kit T. Kilag (Science and Education, 2023)
Abstract: This study investigated the relationship between principal leadership practices and personal development within a school community. The study utilized a mixed-methods approach, including a survey of teachers and students as well as focus group interviews. The quantitative results indicated that principal leadership practices, specifically idealized influence and inspirational motivation, were positively associated with personal development. The qualitative results identified four themes that were important in promoting personal development: supportive leadership, collaboration and teamwork, a growth mindset, and personalized learning. The findings of this study suggest that the leadership practices of principals play an important role in fostering personal development within the school community. Principals who exhibit idealized influence and inspirational motivation are able to inspire and motivate their staff and students, which in turn leads to greater personal development. In addition, the qualitative findings suggest that creating a supportive environment, promoting collaboration and teamwork, fostering a growth mindset, and providing opportunities for personalized learning are important factors in promoting personal development. The implications of these findings are significant for school leaders and educators. School leaders should focus on creating a supportive environment that fosters collaboration and teamwork, promotes a growth mindset, and provides opportunities for personalized learning. By doing so, they can help to foster personal development within their school community, which can have positive implications for student achievement and well-being. Educators should also be aware of the importance of these factors and work to incorporate them into their teaching practices. This study contributes to the understanding of the relationship between principal leadership practices and personal development within the school community. Further research is needed to explore the specific mechanisms by which principal leadership practices impact personal development and to investigate the long-term effects of personal development on student achievement and well-being.